Kearifan Mandailing dalam Tradisi Markobar - FAUZIAH KHAIRANI (BAHAS, 2014)
Oral tradition and oral lore is cultural material and tradition transmitted orally from one generation to another. The messages or testimony are verbally transmitted in speeches or songs and may take the form of folktales, sayings, ballads, songs, or chants. In this way, it is possible for a society to transmit oral history, oral law and other knowledge across generations without a writing system. Markobar is one of the oral traditions that lives in mandailing society which conveys many good values. In spite of its being useful for the community as a guidance to talk and act, it gradually dies down. Sad to say that in some occasions Markobar is carried out by unskilful people and it is done basically for money. There are several things that we can do to keep the well -being of this oral tradition namely by inserting it in the local curriculum and by publishing more books about oral traditions, as for the instances. Key words: oral tradition, markobar, Mandailing, values, curriculum, publishing books